THE ROLE OF INTERPRETER IN DEVELOPING INTERNATIONAL TRADING OF RATTAN FURNITURE: A CASE STUDY AT TRANGSAN VILLAGE, GATAK, SUKOHARJO - Anam Sutopo (Kajian Linguistik dan Sastra, 2006)
The purposes of this study are to find the role of interpreter in developing inter- national trading of rattan furniture and the type of interpreting that they applied in doing their task. The data are taken by using an open-questionnaire, in depth inter- viewing, observation and content analysis. The technique of data analysis is Inter- active Analysis. The result shows that interpreting has a great role in developing the international trading, especially for businessmen who do not master English. It will help them increase their selling products. There are also four roles of inter- preter in developing the international trading of rattan furniture at Trangsan, Gatak, Sukoharjo: interpreter as insparator, mediator, explanator and guide. The inter- preter only applies two types of interpreting: sight and consecutive interpreting. Key words: Interpreter, International Trading, and Rattan Furniture.